2018
DOI: 10.1177/0891243218783670
|View full text |Cite
|
Sign up to set email alerts
|

Re-Understanding Religion and Support for Gender Equality in Arab Countries

Abstract: Much is said about Middle Eastern and North African (MENA) publics opposing gender equality, often referring to patriarchal Islam. However, nuanced large-scale studies addressing which specific aspects of religiosity affect support for gender equality across the MENA are conspicuously absent. This study develops and tests a gendered agentic socialization framework that proposes that MENA citizens are not only passively socialized by religion but also have agency (within their religiosity). This disaggregates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 54 publications
4
95
1
Order By: Relevance
“…Zooming in on Islam, Alexander and Welzel (2011), for example, found that 'Muslim support for patriarchal values is robust against various controls', identifying 'mosque attendance as a mechanism to sustain Muslim support for patriarchy in non-Muslim societies ' (249). Similarly, in a more refined analysis of this linkage, Glas, Spierings, and Scheepers (2018) show that several dimensions of Islamic religiosity (e.g. attending religious service and devotion) fuel opposition towards gender equality in the Middle East.…”
Section: Religiosity and Gender Equality Attitudesmentioning
confidence: 92%
See 3 more Smart Citations
“…Zooming in on Islam, Alexander and Welzel (2011), for example, found that 'Muslim support for patriarchal values is robust against various controls', identifying 'mosque attendance as a mechanism to sustain Muslim support for patriarchy in non-Muslim societies ' (249). Similarly, in a more refined analysis of this linkage, Glas, Spierings, and Scheepers (2018) show that several dimensions of Islamic religiosity (e.g. attending religious service and devotion) fuel opposition towards gender equality in the Middle East.…”
Section: Religiosity and Gender Equality Attitudesmentioning
confidence: 92%
“…At the same time, there have been deviating findings, and it has become clear that different dimensions of religiosity play different roles (Glas, Spierings, and Scheepers 2018;Spierings 2018). To understand how religiosity, gender equality, and migration interrelate, first we have to conceptually distinguish between two core dimensions of religiosity (cf.…”
Section: Religiosity and Gender Equality Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…In including this measure, we indirectly control for how conservative or liberal the values of the parents are. Studies on Muslim populations show strong effects of the degree of religiosity on traditional values about gender, marriage, and sexuality (Diehl and Koenig 2013;Diehl, Koenig, and Ruckdeschel 2009;Glas, Spierings, and Scheepers 2018;Halman and van Ingen 2015). Adjusting the effect of the child's cultural values and behaviours for the effect of the parent's degree of orthodoxy in a multivariate model is analytically similar to estimating effects of parent-child differences in cultural integration.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%